2018
DOI: 10.1038/nature25508
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of tropical forest fragmentation

Abstract: Remote sensing enables the quantification of tropical deforestation with high spatial resolution. This in-depth mapping has led to substantial advances in the analysis of continent-wide fragmentation of tropical forests. Here we identified approximately 130 million forest fragments in three continents that show surprisingly similar power-law size and perimeter distributions as well as fractal dimensions. Power-law distributions have been observed in many natural phenomena such as wildfires, landslides and eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
334
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(351 citation statements)
references
References 31 publications
8
334
1
8
Order By: Relevance
“…As fragmentation is increasing over all tropical forests (Taubert et al. ), our index D disturbance , in addition to the classical fragmentation analysis, can provide valuable information to guide the conservation of the Atlantic Rain Forest in particular and Neotropical forests in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As fragmentation is increasing over all tropical forests (Taubert et al. ), our index D disturbance , in addition to the classical fragmentation analysis, can provide valuable information to guide the conservation of the Atlantic Rain Forest in particular and Neotropical forests in general.…”
Section: Discussionmentioning
confidence: 99%
“…Such resolution has revealed that fragmentation is increasing in all tropical forests (Taubert et al. ). However, it is still too coarse to retrieve information regarding species or the distribution of individual trees that can inform on the successional stage, diversity or disturbance levels of these ecosystems, which play key roles in maintaining environmental processes such as the water cycle, soil conservation, carbon sequestration and habitat protection (FAO, ).…”
Section: Introductionmentioning
confidence: 99%
“…We include a greater coverage of transportation infrastructure that is known to trigger human encroachment and accelerate ecosystem degradation (Ibisch et al, ) and extractive activities that increasingly cause large‐scale land change (Kiesecker & Naugle, ) and have high impact on biodiversity (Schulze et al, ). Unlike other approaches that rely on categorical land system mapping (Van Asselen & Verburg, ; Ellis & Ramankutty, ) or ad hoc categorical scoring (Sanderson et al, ), our cumulative human modification map (HM c ) supports thresholding along a continuous gradient of land modification values to evaluate landscape structure (Verburg, Asselen, Zanden, & Stehfest, ): a component essential for robust cumulative impact assessments (Halpern & Fujita, ) and fragmentation analyses (Haddad et al, ; Halpern & Fujita, ; Taubert et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…ecotones between forests and grasslands) from human‐created edges. Remote sensing from space provides an unprecedented perspective on changing forest cover, allowing continuous maps to be constructed and spatiotemporal patterns of fragmentation to be analysed (Taubert et al , ). Assessments of forest fragmentation have been completed for many countries including Canada, Chile, China, the Democratic Republic of Congo, India, Malaysia, Myanmar, New Zealand, North Korea, Tanzania, the United Kingdom and the USA (Leimgruber et al , ; Watts, ; Ewers et al , ; Kupfer, ; Abdullah & Nakagoshi, ; Echeverria et al , ; Wulder et al , ; Kang & Choi, ; Reddy et al , ; Kukkonen & Käyhkö, ; Shapiro et al , and Li et al , ).…”
Section: Introductionmentioning
confidence: 99%